Accounting for the warm-up: describing the proportion of total session demands in women`s field hockey - Female Athletes in Motion (FAiM) study - Vescovi, J. D.; Klas (International Journal of Performance Analysis in Sport, 2018)
This study quantified the proportion and absolute amount of total session demands accounted for by the warm-up during female field hockey matches. A U21 national women`s field hockey team was monitored during eight matches with GPS/heart rate monitors. A RM-ANOVA compared the relative and absolute demands of the warm-up and total session across matches. Differences between matches for warm-up and total session demands occurred. The average warm-up accounted for 27 ± 2% of total distance (~2,500 m of ~9,400 m) and 30 ± 2% of total session duration (~39 min of ~130 min). Distances covered during the warm-up accounted for 30 ± 2 (low), 26 ± 4 (moderate), 9 ± 2 (high), and 6 ± 2% (maximal) of the total session distances. Cumulatively, the warm-up contributed ~10, 9, 0.4, and 0.06 km in the respective velocity bands. The warm-up duration in heart rate zones was 37 ± 3 (50-80% HRpeak), 22 ± 9 (80-90%), and 3 ± 4% (>90%) of the respective total session duration, corresponding to cumulative totals of ~250, 50 and 10 min in each heart rate intensity band. The warm-up represents a substantial proportion of the total session demands; showing a decreasing contribution with increasing intensity. These outcomes are important in the context of monitoring accumulated demands during congested field hockey tournament schedules.